Competitive Position and Business Strategy of Sugar Cane Plantation Company (Case Study PTPN X Surabaya) - Kahiyang Ayu; Arief Daryanto; Hendro Sasongko (School of Business, Bogor Agricultural University (SB-IPB), 2018)
This research aims to analyze the position of PTPN X in the sugar industry map in Indonesia and to analyze the priority of business strategy that can be implemented by PTPN X. Data analysis methods used are descriptive analysis, SWOT analysis and Analitycal Hierarchy Process (AHP). The results of the research shows that PTPN X is in the position to expand the business through staged revitalizion and diversification. The strategy priority that can be implemented by PTPN X is improving cooperation with farmers with sugar cane-based agro-industry program, increasing the production of sugar through land expansion and revitalization, diversifying sugarcane-based products, changing the production machines. Managerial implications of the research recommend the improvement of cooperation with farmers with sugar cane-based agro-industry program.Keywords: Sugar, PTPN X, SWOT, AHP